Comparison of the converter systems for a high-voltage variable-frequency AC drive - G.G. Zhemerov; D.S. Krylov; O.V. Ilyina; D.V. Tugay; I.G. Titarenko; A.U. Baru; U.L. Shindnes (Electrical engineering & Electromechanics, 2013)
Matlab-models of two converter systems of an 8 MW AC drive are developed, one based on a self-contained current inverter with cut-off diodes, the other based on a multilevel cascade voltage inverter. By applying virtual simulation, qualitative characteristics of these systems are compared.